Development of mango flavored Soy Dahi - Rakhi, TA; Islam, MN; Hoque, SAM; Rahman, MM (Bangladesh Journal of Animal Science, 2013)
The experiment was aimed to prepare mango flavored soy milk based dahi (whole cow milk : soy milk=1:1). To remove the beany flavour of soybean as well as to add the mango flavour, mango juice were added at the rate of 0, 5, 10 and 15%. Data on physical and chemical parameters were recorded and analyzed. It was observed that smell and taste, body and consistency, color and appearance as well as total score were significantly increased (p<0.01) when 5% mango juice added to soy milk based dahi. These properties could further be increased significantly (p<0.01) by increasing the level up to 10% but increasing the level of mango juice up to 15% were significantly decreased (p<0.01) the physical properties. After chemical analysis, a significant increasing (p<0.05) in acidity, total solids and carbohydrate content but a significantly decresing (p<0.05) in fat and ash content of dahi were observed due to the addition of mango juice. Compilation of physico-chemical properties it was observed that addition of 10% mango juice prepared a high quality low cost mango flavored soy milk based dahi. Considering the shortage along with high price of milk we could transfer the techniques to the manufacturer to produce and market the mango flavored soy milk based dahi. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15779 Bang. J. Anim. Sci. 2013. 42 (1): 44-48